Contracting Benefits of Corporate Giving: An Experimental Investigation - Balakrishnan, Ramji; Sprinkle, Geoffrey B.; Williamson, Michael G. (The Accounting Review, 2011)
ABSTRACT We use a laboratory experiment to examine whether corporate giving to charity motivates employees. We find a strong altruism effect. Even when employees cannot be remunerated for their actions, employee contributions to employers significantly increase as the level of corporate giving increases. We also find a signaling effect. When employees can be remunerated for their actions, employee contributions initially increase as the level of corporate giving increases. Thus, even though corporate giving to charity decreases the amount that can be shared between employees and employers, employees behave as if more charitable employers will return proportionally more to employees. It is not until relatively high levels of corporate giving that employee contributions to employers eventually decrease. Collectively, our results suggest that corporate giving is an effective lever for motivating employee effort and contributions to organizational endeavors. Corporate giving can increase the efficacy of implicit (relational) contracts and reduce the need for formal accounting-based reward systems and controls.